1995
DOI: 10.3358/shokueishi.36.50
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Several Organic Acids Commonly Used as Food Additives

Abstract: Among 9 organic acids commonly used as food additives in Japan, fumaric acid (FA) exhibited the strongest growth-inhibiting (GI) action on 20 Gram-negative bacterial strains tested. Growth of these 20 strains, including 3 Salmonella serovars, Escherichia coli, E. cloacae, Klebsiella oxytoca, K. pneumoniae, Acinetobacter anitratus, Proteus mirabilis, or Pseudomonas aeruginosa, was inhibited within 160 seconds of contact with 0.3 w/v% solution of FA, although strains of S. Typhimurium exhibited lower susceptibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Esters of fumaric acid have also been reported to retard mould growth on bread (HUHTANEN and GUY, 1984). SHIMUZU et al (1995) reported that among 9 organic acids commonly used as food additives in Japan, fumaric acid exhibited the strongest growth inhibiting action within 160 s of contact with 0.3% (w/v) solution on 20 gram negative bacteria tested. Fumaric acid at a concentration of 1% (w/v) was the most effective than acetic or lactic acids in reducing the populations of Listeria monocytogenes by up to 1 log unit and E.coli O157:H7 by up to 1.3 log units on lean beef surfaces (PODOLAK et al, 1996b).…”
Section: -Introductionmentioning
confidence: 99%
“…Esters of fumaric acid have also been reported to retard mould growth on bread (HUHTANEN and GUY, 1984). SHIMUZU et al (1995) reported that among 9 organic acids commonly used as food additives in Japan, fumaric acid exhibited the strongest growth inhibiting action within 160 s of contact with 0.3% (w/v) solution on 20 gram negative bacteria tested. Fumaric acid at a concentration of 1% (w/v) was the most effective than acetic or lactic acids in reducing the populations of Listeria monocytogenes by up to 1 log unit and E.coli O157:H7 by up to 1.3 log units on lean beef surfaces (PODOLAK et al, 1996b).…”
Section: -Introductionmentioning
confidence: 99%